Synthesis of Ni/CaO-γ-Al2O3@Ru Core Shell via Micro-Emulsion Method for Bio-oil Steam Reforming of Empty Fruit Bunch - Desi Riana Saputri; Widodo Wahyu Purwanto (Department of Chemical Engineering, Universitas Gadjah Mada, 2018)
Hydrogen production from bio-oil steam reforming plays an important role in the development of renewable hydrogen from biomass to produce the cleanest fuel. However, the existence of coke and low carbon conversion are problems that have been found in some studies. The purpose of this study was to reduce coke formation and to enhance carbon conversion by using core shell nanoparticle catalysts that could increase of surface area, support interaction and its catalytic activity for hydrogen production from bio-oil steam reforming of empty fruit bunch (EFB). Ni/CaO-γ-Al2O3@Ru core shells were prepared by CTAB/n-hexanol/n-hexane/water micro-emulsion system. The catalysts were characterized by means XRD, BET, FESEM-EDS and TEM. Bio-oil aqueous fraction was analyzed by using GC-MS. Carbon conversion and hydrogen yield by using Ni/CaO-γ-Al2O3@Ru core shell are resulted more 68.4 % and 18.6% than using Ni/CaO-γ-Al2O3 catalyst, respectively. The highest hydrogen yield by using Ni/CaO-γ-Al2O3@Ru core shell for steam reforming bio-oil is 5.6% in minute 10 with 0.07 g of coke deposit. The study concludes that the effect of Ni/CaO-γ-Al2O3@Ru core shell is more efficient in hydrogen production, carbon conversion and coke deposit compared to Ni/CaO-γ-Al2O3 catalyst